Framework Towards Enhancing Adoption of Electronic Payment in a Developing Economy: A Case of Uganda - Eelu, Samuel; Nakakawa, Agnes (The African Journal of Information Systems, 2018)
Usage of electronic payment (e-payment) in developing economies is still limited, yet literature reveals several models and research efforts that explain adoption of innovations associated with information and communication technologies. Thus, this paper investigates issues hindering increased adoption of e-payment systems in a developing economy (specifically Uganda), and suggests possible strategic capabilities or interventions that key stakeholders can actualize to address the issues and enhance e-payment adoption. To achieve this, participatory action research was adopted and instantiated by: conducting an exploratory survey to gain relevant insights from target users of e-payment, devising a framework basing on survey findings and on a literature-based taxonomy of aspects that influence technology adoption, and evaluating the artifact using structured walk through with domain experts. Accordingly, the framework presented herein not only explains dynamics in e-payment adoption, but also informs and directs stakeholders on required interventions towards enhancing adoption of e-payment in a developing economy.
Keywords: Adoption of Electronic Payment Systems; Information Technology Adoption; Strategic Interventions for Electronic Payment Systems